Antibakteri pada Formulasi Sediaan Sabun Mandi Kombucha Bunga Telang (Clitoria ternatea L) sebagai Produk Bioteknologi Farmasi - Firman Rezaldi; Siska Dwi Anggraeni; Aris Ma'ruf; Muhammad Andry; Hendri Faisal; Hanafis Sastra Winata; Indra Ginting; Muhammad Amin Nasution (Jurnal Biotek, 2023)
Copyright©2023 Liquid soap with the active ingredient kombucha butterfly pea can limit the growth of Staphylococcus epidermidis and Pseudomonas aeruginosa bacteria. The purpose of this research was to create a liquid bath soap with the active ingredient fermented liquid from the kombucha flower of the butterfly pea plant that inhibits the development of the two test bacteria and to provide objective data on the maximum inhibitory energy at the concentration of the bath soap preparation that can limit the growth of the two test bacteria. This research was experimental and involved making four different types of bath soap preparations: soap base (negative control), liquid body soap formulated with butterfly pea flower kombucha at concentrations of 20, 30, and 40%, and one of the commercial soaps (positive control). Disc diffusion is the method for measuring the average growth of the two test bacteria. Statistical analysis was a one-way ANOVA statistical test at a 95% confidence level, followed by post hoc analysis. The research showed that the liquid body soap with the active ingredient of telang flower kombucha could positively inhibit the growth of the two test bacteria. The concentration of 40% telang flower kombucha bath soap is the best concentration to limit the development of the two test bacteria, with an inhibition zone of 10 mm on Staphylococcus epidermidis, which is in the strong category, and an inhibition zone of 7 mm on Pseudomonas aeruginosa, which is classified as a moderate category.